Penolakan Isbat Syawal di Jepara dan Cakung Tahun 1432 H Perspektif Hukumah dan Astronomi - Muhammad Zaki Mubarok; Youla Afifah Azkarrula (Astroislamica: Journal of Islamic Astronomy, 2023)
Hisab by Mujab in Jepara produced Hilal’s height 1.5° and was visible. While, two Al-Husainiyyah students in Cakung who use hisab from Nayiroain Sullamun which produced Hilal’s height 3° and was visible. With these things, it raises questions, about the legal and astronomical review of the results of the rukyat at the end of Ramadan in 2011 AD/1432 H in Jepara and Cakung. This type of research is a literature study with qualitative research. In analyzing the data, the authors used a descriptive approach because the data was obtained qualitatively. The data collection techniques through documentation and interviews. The author conducted interviews with perukyat, judges who took the oath and some experts in Falak science. The results showed that based on legal analysis, the two places of rukyatul hilal in Jepara and in Cakung were legally rejected because the Ministry of Religion was guided by some covenants; the implementation of the two places are not in accordance with the SOP so the Ministry of Religion in isbat depends on astronomy experts, Falak and BMKG. Meanwhile, based on astronomical analysis, the testimony of rukyatul hilal in Jepara and in Cakung can be rejected because they do not match the MABIMS criteria.